LARVICIDAL ACTIVITY OF Garcinia mangostana FRUIT WASTES AGAINST DENGUE VECTOR Aedes aegypti - R. C. Torres; A. G. Garbo; R. Z. M. L. Walde (Journal of Animal and Plant Sciences, 2015)
This study was conducted to investigate the effect of the ethanol and hexane extracts of the fruit wastes of Garcnia mangostana (mangosteen) on the Dengue vector Aedes aegypti.The fruit wastes (pericarp, crown and seeds) were solvent extracted separately. The larvicidal activity of the extracts was tested against the 3rd and 4th instars larvae of the Aedes aegypti following the World Health Organization bioassay method (2005). Characterization of the extracts was conducted by qualitative phytochemical screening. The ethanol pericarp extract of G. mangostana exhibited the highest toxicity among the other parts (crown and seeds) against A. aegypti larvae with an LC50 values of 4.84 mg/L and 6.19 mg/L and LC90 values of 14.55 mg/L and 28.71 mg/L while the hexane extract yielded an LC50 and LC90 of 27.61 mg/L and 67.27 mg/L, respectively. The hexane crown extract also yielded larvicidal activity with an LC50 and LC90 of 25.33 mg/L and 63.73 mg/L, respectively while the ethanol extract gave an LC50 of 63.00 mg/L and LC90 of 169.91 mg/L. Meanwhile, both ethanol and hexane extracts of the seeds did not exhibit any toxic effect up to 500 mg/L and 300 mg/L, respectively. Results suggest the potential of G. mangostana fruit wastes as a key source for the development of environment-friendly plant-based larvicides.
Keywords: Garcinia mangostana; dengue vector; Aedes aegypti; larvicidal activity; phytochemical screening